2006
DOI: 10.4314/ajesms.v1i1.38574
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alternative assessment on the attitudes and achievement in mathematics of female pre-service teachers in Ghana

Abstract: This paper examines the effect of exposing one of two groups of preservice female teachers to alternate forms of assessment. Both groups were first year students in a teacher training college and received 8 weeks of normal instruction in mathematics content and traditional assessment by the same teacher. The students were interviewed on their attitudes towards mathematics before and after instruction. In addition, the students took two pretests and corresponding posttests. The external achievement tests were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, Table 4 also shows that the weakest areas for the control group was in "From these functions, determine the one with the minimum vertex (2,3)." B) * = (" − 2) !…”
Section: Identification Of the Coordinates Of Vertex (Turning Point)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Table 4 also shows that the weakest areas for the control group was in "From these functions, determine the one with the minimum vertex (2,3)." B) * = (" − 2) !…”
Section: Identification Of the Coordinates Of Vertex (Turning Point)mentioning
confidence: 99%
“…Meanwhile the teaching and learning of Mathematics especially algebra in schools have been perceived as difficult [1] especially in Africa of which Ghana is not an exception. This notion has resulted to students' poor performance in the subject at the Junior High School (BECE) and Senior High School levels [2], [3]. The poor performance of Mathematics (emphasis on algebra) has been attributed to non-integration of ICT into teaching and learning [4], [5], non-changed learning methods [6], [7], over concentration on teacher centered approaches in teaching [7], differences in pedagogical orientation [8] and other compelling factors.…”
Section: Introductionmentioning
confidence: 99%
“…Eshun (1999) also reported that in general, students had positive attitudes towards mathematics especially along the attitudinal variables, usefulness of mathematics, like doing mathematics, and experience of success in mathematics. Eshun and Abledu (2001) revealed that students are however least positive about effective motivation, and confidence in doing mathematics. They concluded that students' low achievement in mathematics could partly be attributed to lack of motivation and confidence to learn the subject.…”
Section: Introductionmentioning
confidence: 99%